If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 6 + 2x + (4x + -8) = 62 Reorder the terms: 2x + 6 + 2x + (-8 + 4x) = 62 Remove parenthesis around (-8 + 4x) 2x + 6 + 2x + -8 + 4x = 62 Reorder the terms: 6 + -8 + 2x + 2x + 4x = 62 Combine like terms: 6 + -8 = -2 -2 + 2x + 2x + 4x = 62 Combine like terms: 2x + 2x = 4x -2 + 4x + 4x = 62 Combine like terms: 4x + 4x = 8x -2 + 8x = 62 Solving -2 + 8x = 62 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 8x = 62 + 2 Combine like terms: -2 + 2 = 0 0 + 8x = 62 + 2 8x = 62 + 2 Combine like terms: 62 + 2 = 64 8x = 64 Divide each side by '8'. x = 8 Simplifying x = 8
| 13*(9-6)=n | | Y=4/9x-3 | | 5u-6+5(2u+3)=-3(u+1) | | 7(2x-3)=3(3x-11) | | 4xsquared=144 | | z-4+9=6 | | -1.476-1.6a=3.6a-0.28 | | z-4+ 9= 6 | | s^2+20s-17=0 | | u^2-28u=-15 | | 23.18+5.8= | | lnx^7-5lnx-2=0 | | y=3x^2+5x-300 | | y^2+2y-11=0 | | 2x(x-1)+3(x-1)=0 | | 28x^2+7x=0 | | 40.8/4 | | 3x-32+3x+2=180 | | s+50(6)=3s | | 2x^2+2y^2+4x-16y+26=26 | | t^2-4t=9 | | 4x+9+3x+3=180 | | j^2+6j=5 | | x+3.4=6.6 | | -12=6y+24 | | x^2+16x+37=0 | | f(x)=0.3(x^2-4x) | | 12x+2x-6y+2y-4x= | | 22=2t+2d | | 360.40-0.06(p)=p | | p^2+8p=25 | | 14-19= |